2011
DOI: 10.1017/s1751731111000450
|View full text |Cite
|
Sign up to set email alerts
|

Whole body insulin responsiveness is higher in beef steers selected for increased muscling

Abstract: The aim of this experiment was to evaluate the impact of selection for greater muscling on whole body insulin responsiveness in cattle, as reflected by greater uptake of glucose in response to constant insulin infusion and greater glucose disappearance following an intravenous glucose tolerance test. This study used 18-month-old steers from an Angus herd visually assessed and selected for divergence in muscling over 15 years. Eleven high-muscled (High), 10 low-muscled (Low) and 3 high-muscled steers, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Shift in fibre type proportions is likely to lead to metabolic changes in muscle, as has been shown by McGilchrist et al (2011aMcGilchrist et al ( , 2011b and Martin et al (2011) who demonstrated that more muscular cattle and lambs are more responsive to insulin, less responsive to adrenaline and had a higher storage of muscle glycogen (McGilchrist, et al, 2011a). Therefore younger cattle and more muscular cattle are both likely to have increased glycogen at slaughter and a reduced incidence of dark cutting syndrome.…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…Shift in fibre type proportions is likely to lead to metabolic changes in muscle, as has been shown by McGilchrist et al (2011aMcGilchrist et al ( , 2011b and Martin et al (2011) who demonstrated that more muscular cattle and lambs are more responsive to insulin, less responsive to adrenaline and had a higher storage of muscle glycogen (McGilchrist, et al, 2011a). Therefore younger cattle and more muscular cattle are both likely to have increased glycogen at slaughter and a reduced incidence of dark cutting syndrome.…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
“…McGilchrist et al (2011b) has shown that Angus cattle selected for high muscling had increased whole body insulin responsiveness. This may enhance the uptake of glucose into muscle tissue in the postprandial period and allow for an increased rate of glycogenesis, allowing these animals to have higher resting concentrations of muscle glycogen (McGilchrist, et al, 2011a).…”
Section: Effect Of Musclingmentioning
confidence: 99%
“…Cattle that have predominantly β (Type I)‐red and α (Type IIA)‐red muscle fibers tend not to be heavily muscled, because β‐ and α‐red muscle fibers are smaller than α‐white (Type IIB) glycolytic fibers (Schiaffino ); therefore, cattle that are small and lightly muscled may be at heightened risk of DC because their muscle fibers are more easily depleted of glycogen with the same level of activity or stress compared with an animal with α‐white muscle fibers (McGilchrist and others. ,b). Also, Tarrant () indicated that muscles most likely to be dark in a beef carcass due to physical stress, were those that had the largest proportion of fast glycolytic muscle fibers, such as the longissimus thoracis et lumborum (LTL) and semitendinosus (ST), whereas those that responded to adrenaline administration, and hence most likely to be depleted by anxiety, were the slow‐twitch β‐red muscle fibers.…”
Section: Contributing Factors To DCmentioning
confidence: 99%
“…However, in spite of numerous studies [ 10 19 ], it has not been possible, hitherto, to identify markers which allow a breeder to quantify superior genetics in individual sires and dams. Some of the explanations for the slow progress include the following: Complexity due to interactions of several metabolic processes and their regulatory mechanisms [ 6 , 20 , 21 ]. Contribution of many genes with small effects [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complexity due to interactions of several metabolic processes and their regulatory mechanisms [ 6 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%